AB0474 MORTALITY ACROSS RITUXIMAB-TREATED PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: RESULTS FROM THE BRITISH ISLES LUPUS ASSESSMENT GROUP (BILAG) REGISTRY. (June 2019) - Aksoy, Aysun; McDonald, Stephen; Mccarthy, Eoghan; Parker, Ben; Bruce, Ian N.; ,
Abstract : Background: Mortality in Systemic Lupus Erythematosus (SLE) is elevated in comparison to the general population. Previously we have demonstrated improved disease control in response to Rituximab (RTX) therapy in a cohort of refractory SLE patients. Objectives: To investigate mortality in refractory SLE patients treated with RTX and identify risk factors that may be associated with death. Methods: All patients recruited to the BILAG-BR (both RTX treated and standard of care-SOC) were included from initial study visit to death or 3 years post last treatment change. Demographics, concurrent medication use, disease activity (BILAG/SLEDAI) and damage scores (SLICC-DI) were recorded. Information regarding mortality was collected from study centres and NHS digital national death registry. Baseline demographic data are presented using descriptive statistics performed using Stata (version 14). Results: 830 patients were included (715 RTX-treated, 115 standard therapy). RTX-treated patients tended to have longer disease duration (10 vs 6.5 years respectively) and were more likely to have active musculoskeletal disease (% BILAG A or B: 39% vs 23%). Rates of renal (11% vs 16%) and neurological disease (12% vs 9%) were comparable between groups as were baseline SLICC-DI and SLEDAI scores. 33 deaths were reported. 28 (3.9%) RTX-treated patients (1.2 deaths/100 pt yrs follow up) and 5 (4.3%) non-RTX patients (1.5 deaths/100 pt yrs follow up). Cause of death was identifiable in 20 RTX treated patients. Infection was the commonest cause of death (10/20, 50%) followed by ischaemic heart disease (5/20, 25%) and malignancy (3/20, 15%). Median time to death for RTX-treated was 481 days. Risk factors associated with mortality within the RTX group included male gender, older age at diagnosis, renal disease, hypogammaglobulinaemia, high SLICC-DI and higher steroid use at last review (Table 1 ). Median cumulative RTX dosing was 2g for deceased and alive. Deceased RTX patients had a greater total number of co-morbidities at baseline (2.5 vs 0, p < 0.01) driven predominantly by the presence of hypertension (11/28, 39% vs 159/687, 25%, p = 0.05), ischaemic heart disease (4/28, 14% vs 11/687, 2%, p= 0.00) and diabetes (7/28, 25% vs 15/687, 2%, p = 0.00). Conclusion: RTX treated patients do not appear to have higher mortality rates compared to patients starting SOC treatment. Mortality is associated with cardiovascular risk factors, higher steroid doses, hypogammaglobulinaemia and renal disease. Active management of these risk factors may lead to improved mortality outcomes. Disclosure of Interests: Aysun Aksoy: None declared, Stephen McDonald: None declared, Eoghan McCarthy: None declared, Ben Parker Grant/research support from: GSK, Consultant for: AZ, UCB, GSK, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GlaxoSmithKline, Consultant for: AstraZeneca, Eli Lilly, GlaxoSmithKline, ILTOO Pharma, MedImmune, Merck Serono, Speakers bureau: GlaxoSmithKline, UCB Pharma